Analysis Of Completeness Of Outpatient Integrated Patient Development Note Form Completion At Internal Medicine Polyclinic According To Soap At Rsud Dr. R.M. Djoelham Binjai - Yudica Rosalina; Lenni Irawati; Yusriwan Tjuanda (Sean Institute, 2024)
A method of documenting a progress patient note explicates three details, including what happened to the patient, what is planned for the patient & how the patient reacts to the therapy being taken. The documentation method employs four steps regarding a systematic decision-making process, known as SOAP which is an acronym for Subjective, Objective, Assessment, and Plan. Based on a previous study conducted at the medical record installation of Dr. R.M. Djoelham General Hospital in Binjai, there was still incomplete documentation on the forms of the patient progress notes integrated outpatient care by SOAP. Objectives: To find out the percentage of the completeness and incompleteness in filling out the outpatient integrated progress note forms according to SOAP and to determine the factors causing the completeness and incompleteness of filling out the forms according to SOAP at Dr. R.M. Djoelham General Hospital in Binjai.